Regionally adaptive physical training for university students considering environmental and social disparities - Kondratenko, Svetlana; Tuyakbaeva, Meruert; Madiyeva, Galiya; Arkabaeva, Saule; Zhalel, Ali; Shepetyuk, Natalia (Frontiers in Public Health, 2025)
Airborne polycyclic aromatic hydrocarbons (PAHs) are urban combustion by-products linked to endocrine disruption, but their direct molecular interactions with testosterone remain under-characterized. Using DFT [B3LYP/6–311 + G(d,p)] and 10-ns all-atom MD, we quantified non-covalent binding between benzene, naphthalene, and anthracene and testosterone, observing size-dependent stabilization (anthracene most favorable). Complementary MEP, Mulliken charge, and FMO analyses indicated progressive electronic coupling consistent with π–π and hydrophobic packing. In a semester-long controlled program with male university students (n = 60), we compared identical training conducted in a polluted urban area (PM2.5 > 50 μg·m−3) vs. a suburban green zone (PM2.5 < 10 μg·m−3) and observed larger gains in 100-m sprint, pull-ups, and standing long jump under cleaner air. We now report 95% confidence intervals alongside effect sizes for all field outcomes and provide a correlation between pollution intensity and performance change. PM2.5 was used as an operational exposure index because combustion-related PAHs predominantly partition to fine particles and co-vary with PM₂.₅ mass in ambient air (WHO guideline context and PAH–PM₂.₅ literature). Collectively, the molecular and field evidence suggests larger PAHs may perturb testosterone function and that cleaner air is associated with better short-term training gains, informing air-quality-aware scheduling and campus policy.